Strategi Pedagogis Guru dalam Pengajaran Mufradat Bahasa Arab di Madrasah Aliyah - Selamet Ryadi; Yeni Nuriah Fitri (Universitas Serambi Mekkah, 2026)
This study aims to analyze teachers’ pedagogical strategies in teaching Arabic vocabulary (mufradāt), identify the factors influencing instructional effectiveness, describe the challenges encountered during instruction, and examine the adaptive strategies employed to address them. A qualitative approach with a case study design was conducted at MA Subulussalam. The participants consisted of the principal, vice principal for curriculum, an Arabic language teacher, and five students selected purposively. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the teacher employed adaptive pedagogical strategies by integrating lectures, demonstrations, memorization, gradual practice, and visual media according to students’ characteristics. Instructional effectiveness was influenced by learning motivation, prior knowledge, the learning environment, and teachers’ pedagogical competence. The main challenges involved differences in students’ initial abilities and limited instructional time. These challenges were addressed through repeated vocabulary practice, contextual learning, continuous reinforcement, and ongoing assessment. The study concludes that the effectiveness of Arabic vocabulary instruction is determined more by teachers’ ability to integrate pedagogical strategies contextually than by reliance on a single teaching method or instructional medium.